The Role of Fine Arts in the Formation of Spiritual and Aesthetic Qualities of Personality - Yunusaliev Mukhamadkodir Tadjimadovich (Scientific Trends, 2025)
The article analyzes the role of fine art in the formation of spiritual and aesthetic qualities of the individual, as well as its educational and artistic-aesthetic potential. By means of art, attention is paid to the issues of educating in the hearts of the younger generation a sense of artistic taste, spiritual elevation, national pride, and devotion to values.
Keywords: Fine arts, spiritual education, aesthetic taste, artistic thinking, national values.